TRIBOEXPERIMENTAL STUDIES OF COMPOSITE ANTIFRICTION POLYMER DK6 AND DK6 + BRONZE FOR TRIBOTECHNIC SLIDING SYSTEMS - Чернець, Мирон Васильович; Корнієнко, Анатолій Олександрович; Іщенко, Анатолій Олексійович; Радіоненко, Олександр Васильович (Problems of Friction and Wear, 2021)
The method of model triboexperimental researches of composites DK6 and DK6 + Bronze in pair with steel 45 at sliding friction according to the scheme of end friction is given. Their wear-resistance indicators were experimentally established, according to which the characteristics of their wear resistance at dry sliding friction were determined, as the basic characteristics of the mathematical model of studying the wear kinetics of materials at sliding friction. Also, according to the research, their wear resistance diagrams are constructed as graphical indicators of wear resistance in the accepted range of specific friction forces. It was found that DK6 filled with bronze powder will have a higher wear resistance than DK6 composite up to 38% at a sufficiently specific friction forces. The results of determining the coefficients of sliding friction are also given. It was found that in the tribocouple composite DK6 + Bronze - steel the coefficient of sliding friction will be slightly lower (up to 6%) than in the tribocouple composite DK6 - steel.